دور القاضي الإداري في مواجهة الإدارة على أعمال التعدي - صوالح, أبو بكر; مسعودي, محمد البشير; زوي, محمد (University of Eloued جامعة الوادي, 2023)
تعتبر نظرية التعدي من بين النظريات التي تصورىا القضاء الإداري الفرنسي مع بداية القرن التاسع عشر، حيث تيدف إلى توقيع الج ا زء من بعض الأفعال والتصرفات المادية ذات الطابع التنفيذي التي تتصف بعدم مشروعية جسيمة، وتمس حق من حقوق الممكية أو حرية أساسية. وقد عرفت ىذه النظرية تطو ا ر عمى المستوى القضائي، فيمكن القاضي المختص في المنازعة سواء، القاضي الإداري في الج ا زئر، أو القاضي العادي في فرنسا أن يجرد الإدارة من الامتيا ا زت التقميدية التي تتمتع بيا، وعميو يمكن لمقاضي وقف تنفيذ الق ا رر محل الطعن، وتوجيو أوامر إلى الإدارة إضافة إلى اقت ا رن الأوامر بغ ا رمات تيديدية.The theory of infringement is among the theories conceived by the French administrative judiciary at the beginning of the nineteenth century, as it aims to impose the penalty for some acts and material behaviors of an executive nature that are characterized by gross illegality, and affect the right of property rights or fundamental freedom. This theory has known development at the judicial level, so the competent judge in the dispute, whether the administrative judge in Algeria, or the ordinary judge in France, can strip the administration of the traditional privileges that it enjoys, and accordingly the judge can stop the implementation of the decision in question, and direct orders to the administration in addition The orders lead to threatening fines.
مذكرة ماستر
Keywords: تصرف مادي تعدي إدا رة استعجال قاضي الاستعجال الإداري - - - - وقف التنفيذ أوامر غ ا رمة تيديدية.; material behavior - transgression - administration - urgency - administrative emergency judge - suspension of execution - orders - threatening fine.